Improved Teacher Performance Through Work Culture And Environment - Lutfah, Asma; Hariyati, Nunuk; Handayaningrum, Warih (Universitas Malikussaleh, 2019)
The existence of teachers in the world of education has a great influence to produce excellent students. Based on the law Republic of Indonesia Number 14 of 2005 about Teachers and Lecturers, who stated that teachers and lecturers have functions, roles, and a very important position in national development in the field of education, so it needs to show that its performance can be accounted for. Performance improvement is closely related with the problem of how to increase teacher motivation, how to develop an effective work culture as well how to create a work environment that is comfortable and conducive, so that the teacher can and is willing to work optimally. According to Nitisemito (1991: 184-196), influencing factors work environment is coloring, cleaning, lighting, air exchange, music, safety and noise. while work culture factors that influence are: (1) conditions the physical environment of work, such as giving awards, giving welfare, fulfilling infrastructure and facilities. (2) working environment conditions, such as support in carrying out tasks, communication and interactions with peers, people student parents, principal and public. For that, schools must be able creating a conducive work environment and work culture.